Situasi dalaman Indonesia menjelang Kudeta 30 September 1965 - Rohani Abd Ghani, (Penerbit UKM, 2007)
The three major elements determining the development of the Indonesia coup d’etat 30th of September 1965 were Sukarno, military and the Communist Party of Indonesia (PKI). The power competition between the army and PKI to some extent was attributable to President Sukarno, who sought to use each side to balance and counter-check one another. On the part of the military and PKI, they saw the President as a key factor to the future power design in Indonesia. This article discusses the impact of internal situation such as domestic politics and Sukarno’s health problem on Indonesia’s political development. The discussion also touches upon the British strategy to combat communism and to end the Konfrontasi between Malaysia and Indonesia. The paper relies primarily on British official records from the National Archive, Kew, London.